Differentiation of acute myeloid leukemia (AML) cells with ATRA reduces 18F-FDG uptake and increases sensitivity towards ABT-737-induced apoptosis. Issue 3 (23rd February 2021) - Buschner, Gabriel; Feuerecker, Benedikt; Spinner, Sabine; Seidl, Christof; Essler, Markus
Abstract: Acute myeloid leukemia (AML) is a malignant disease of the bone marrow, comprising various subtypes. We have investigated seven different AML cell lines that showed different sensitivities toward the inducer of apoptosis ABT-737, with IC50 concentrations ranging from 9.9 nM to 1.8 µM. Besides, the AML cell lines revealed distinct differences in 18 F-FDG uptake ranging from 4.1 to 11.0%. Moreover, the Pearson coefficient (0.363) suggests a moderate correlation between 18 F-FDG uptake and the IC50 values of ABT-737. Differentiation of the AML cell lines NB-4 and AML-193 with all-trans-retinoic-acid (ATRA) induced a significant increase in sensitivity towards ABT-737 along with a reduced uptake of 18 F-FDG. Therefore, 18 F-FDG uptake could be predictive on sensitivity to treatment with ABT-737. Furthermore, because differentiation treatment of AML cells using ATRA reduced 18 F-FDG uptake and increased sensitivity towards ABT-737, a combined treatment regimen with ATRA and ABT-737 might be a promising therapeutic option in the future.